Networks and Misallocation: Insurance, Migration, and the Rural-Urban Wage Gap - Kaivan Munshi; Mark Rosenzweig (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2015)
We provide an explanation for the large spatial wage disparities and low male migration in India based on the trade-off between consumption-smoothing, provided by caste-based rural insurance networks, and the income-gains from migration. Our theory generates two key empirically-verified predictions: (i) males in relatively wealthy households within a caste who benefit less from the redistributive (surplus-maximizing) network will be more likely to migrate, and (ii) males in households facing greater rural income-risk (who benefit more from the insurance network) migrate less. Structural estimates show that small improvements in formal insurance decrease the spatial misallocation of labor by substantially increasing migration.
Keywords: 330